The pro‐apoptotic Bax gene modifies susceptibility to craniofacial dysmorphology following gastrulation‐stage alcohol exposure. Issue 19 (9th April 2022) - Fish, Eric W.; Mendoza‐Romero, Haley N.; Love, Charlotte A.; Dragicevich, Constance J.; Cannizzo, Michael D.; Boschen, Karen E.; Hepperla, Austin; Simon, Jeremy M.; Parnell, Scott E.
Abstract: Background: During early development, alcohol exposure causes apoptotic cell death in discrete regions of the embryo which are associated with distinctive patterns of later‐life abnormalities. In gastrulation, which occurs during the third week of human pregnancy, alcohol targets the ectoderm, the precursor of the eyes, face, and brain. This midline tissue loss leads to the craniofacial dysmorphologies, such as microphthalmia and a smooth philtrum, which define fetal alcohol syndrome (FAS). An important regulator of alcohol‐induced cell death is the pro‐apoptotic protein Bax. The current study determines if mice lacking the Bax gene are less susceptible to the pathogenic effects of gastrulation‐stage alcohol exposure. Methods: Male and female Bax +/− mice mated to produce embryos with full ( −/− ) or partial ( +/− ) Bax deletions, or Bax +/+ wild‐type controls. On Gestational Day 7 (GD 7), embryos received two alcohol (2.9 g/kg, 4 hr apart), or control exposures. A subset of embryos was collected 12 hr later and examined for the presence of apoptotic cell death, while others were examined on GD 17 for the presence of FAS‐like facial features. Results: Full Bax deletion reduced embryonic apoptotic cell death and the incidence of fetal eye and face malformations, indicating that Bax normally facilitates the development of alcohol‐induced defects. An RNA‐seq analysis of GD 7 Bax +/+ and Bax −/− embryos revealed 63 differentially expressed genes, some of which may interact with the Bax deletion to further protect against apoptosis. Conclusions: Overall, these experiments identify that Bax is a primary teratogenic mechanism of gastrulation‐stage alcohol exposure.